Correlation of Post-Operative Outcomes in patients undergoing CABG Receiving Antegradecardioplegia alone Versus Combined Antegrade Plus Retrograde Cardioplegia: A Prospective Review - Saima Jabeen, Ahsan Arif, Syeda Rabia Bukhari, Mubashir Umair, Sahar Akbar, Aftab Yunus, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the mean ejection fraction and cardiac enzymes level in patients with Ischemic heart disease undergoing elective coronary artery bypass graft surgery (CABG) having antegrade blood cardioplegia versus antegrade plus retrograde Cardioplegia. Study design: Randomized Controlled Trial Place and duration: This study was performed from 7th February, 2020 to 7th August, 2020 at the Cardiac Surgery Department, PIC, Jail Road, Lahore. Methodology: After receiving informed consent, all patients undergoing CABG were enrolled in this study. In order to compare the mean ejection fraction and cardiac enzyme levels between patients who had antegrade blood cardioplegia and those who had antegrade plus retrograde cardioplegia, preoperative, intraoperative, and postoperative characteristics were recorded into the predesigned proforma. Results: The total number of patients 72 was enrolled in this study who were divided into two groups. There were 36(50%) patients of who have given Cardioplegia through antegrade route while CABG and 36(50%) patients who have given Cardioplegia through antegrade plus retrograde route while CABG in this study. According to Table 1, the mean age of the patients in Group A was 51.86±9.35 years, whereas the mean ages of the participants in Group B 52.92±7.70 years. There were 26(72%) male and 10(28%) females in Group A and 30(83%) male and 6(17%) females in Group B. The mean BMI in Group A was 25.65±5.18 and 25.02±3.97 in Group B. There were 35(97%) hypertensive and 1(3%) non hypertensive patients in Group A and B respectively. Similarly, there were 33(92%) diabetic and 3(8%) non diabetic patients in Group A and 28 (78%) diabetic and 8(22%) non diabetic patients were in Group B. There were 26(72%) smokers and 10(28%) non- smokers in Group A and 24 (67%) smokers and 12(33%) non-smokers in this Group B. Practical Implication: The comparison of CKMB(IU/L) levels in Antegrade route group and antegrade plus retrograde group baseline and after 48 hours shows insignificant p-values of 0.17 and 0.12 respectively which shows that there is no significant difference in CKMB levels regarding these two routes chosen for giving Cardioplegia to patients undergoing coronary artery bypass grafting. Conclusion: Although both required additional surgical manoeuvres, however, the antegrade and antegrade plus retrograde cardioplegia approaches were equally effective and safe. Prior research demonstrated that multiple infusions offer superior protection to either antegrade or retrograde cardioplegia alone. Keywords: Coronary artery Bypass grafting surgery, Antegrade route, Retrograde Route, Antegrade plus Retrograde route.